Assembly of the Nosiheptide A-Ring: A Fruitful Lesson - Lu, Jin-Yong; Riedrich, Matthias; Wojtas, K. Philip; Arndt, Hans-Dieter (Synthesis, 2013)
The synthesis of a 28-membered thiopeptide macrocycle is described. Key steps are mild aza-Wittig thiazole ring closures, a scandium(III)-mediated regioselective ester hydrolysis, and a highly efficient macrolactam formation with its 3-hydroxypyridine nucleus orthogonally protected.
Keywords: antibiotics; aza-Wittig reaction; heterocycles; natural products; macrocyclization; thiopeptides.